A new species of the genus Acria Stephens, 1834 (Lepidoptera: Depressariidae: Acriinae) from India - Shashank, P.r; Saravanan, L.; Kalidas, P.; Phanikumar, T.; Ramamurthy, V. V.; Bose, N. S.chandra (Zootaxa, 2015)
A new species, Acria meyricki sp. nov. (Lepidoptera: Depressariidae: Acriinae) occurring on oil palm, is described from India. The status and nomenclature of the genus is reviewed and an annotated checklist of species is given. A key to the seven species known so far from the Indian subcontinent is provided.